Natural frequencies of a flat viaduct road part simply supported on two ends - Yüksek, I; Çelik, A; Gülez, K (SPRINGER INDIA, 2006)
Viaduct roads have wide application in big cities with high traffic loads, in order to decrease traffic density and to connect subways to highways. Viaduct roads are constructed using steel structures instead of concrete ones in areas of earthquake risks. The low weight of steel structures however causes problems such as vibration and noise. There is increasing, demand especially in populated areas to suppress vibration and noise on highway roads for reducing noise-related In environmental pollution. In this study, bending vibrations of rectangular plate viaduct roads, which are CD supported by six fixed elements of rectangular cross-sectional elements are considered. Natural frequencies are obtained using the Rayleigh-Ritz technique, finite elements analysis, experimentally and neural networks (NN).
Keywords: bending vibration; natural frequency; rectangular plate; Rayleigh-Ritz technique; neural networks; RECTANGULAR-PLATES; STIFFENED PLATES; FINITE-ELEMENT; FLEXURAL VIBRATION; Engineering